Analisis Pemanfaatan Media Permainan Kartu Huruf untuk Meningkatkan Pemahaman Siswa dalam Pembelajaran PAI pada Siswa Kelas Satu Materi Mari Mengenal Huruf Hijaiyah di SD Islam Khaira Ummah Padang - Farios, Aziz Anugrah (YASIN, 2023)
This research was motivated by the application of letter card learning media to improve the understanding of first grade elementary school students. This research aims (1) To find out how teachers design letter card game media in PAI learning materials, let's get to know the hijaiyah letters for class 1 B students at Khaira Ummah Islamic Elementary School in Padang. (2) To find out how teachers apply letter card game media to PAI learning materials, let's get to know the Hijaiyah letters for class 1 B students at Khaira Ummah Islamic Elementary School, Padang. (3) To find out the advantages and disadvantages of using letter card game media to improve students' understanding of PAI learning material, let's get to know the Hijaiyah Letters for class 1 B students at Khaira Ummah Islamic Elementary School, Padang. This research uses a qualitative descriptive method, the research object is class 1 B students of Khaira Ummah Islamic Elementary School in Padang and the research subject is students' understanding of learning. Then data was obtained from observation, interviews with informants, and documentation to see existing phenomena. The research results showed that first, the teacher designed card media using simple and affordable materials. Second, in the implementation process the teacher explains the learning material using the play while learning method, following the educational standards and curriculum that apply in the school. Third, the advantages and disadvantages of card game learning media are that children really like this media. And the downside is that students have their own way of learning so there are students who experience boredom while studying.